A new species of planthopper in the genus Platocerella (Hemiptera: Auchenorrhyncha: Derbidae) from palms in Costa Rica, a key to the genus and an updated molecular phylogeny of available New World Otiocerinae - Barrantes, Edwin A. Barrantes; Echavarria, Marco A. Zumbado; Bartlett, Charles R.; Helmick, Ericka E.; Bahder, Brian W. (Zootaxa, 2024)
The genus Platocerella is a monotypic otiocerine genus (Derbidae: Otiocerinae: Otiocerini) reported from Guyana. A new species of Platocerella associated with palms is herein described from Costa Rica. Molecular data for the barcoding region cytochrome c oxidase subunit I (COI), 18S rRNA gene, and D9-D10 expansion region of the 28S rRNA gene is provided to produce a preliminary phylogenetic tree including the new species and related taxa to place the new species relative to other otiocerine planthoppers.